Optimal Design and Biomechanical Analysis of a Biomimetic Lightweight Design Plate for Distal Tibial Fractures: A Finite Element Analysis - Wang, Mian; Deng, Yuping; Xie, Pusheng; Tan, Jinchuan; Yang, Yang; Ouyang, Hanbin; Zhao, Dongliang; Huang, Gang; Huang, Wenhua (Frontiers in Bioengineering and Biotechnology, 2022)
The treatment of fractures of the distal tibia can be problematic due to the insubstantial soft-tissue covering this part of the anatomy. This study investigates a novel strategy for minimally invasive plate osteosynthesis of distal tibia fractures called bionic low-profile plating. Following the structure of the animal trabecular bone, bionic low-profile plates utilized topological mathematical methods to redesign the material layout of the address area of the internal fixation device to fulfill the desired low-profile design within given working and boundary conditions. The results showed that this method can maintain the same stability of the construct as the original plate after a reduction in the original volume by 30%, and the differences in strain energy of plates and maximum node displacement of constructs between the constructs (redesign plating [RP] construct vs. locked plating [LP] construct) were not statistically significant (P > 0.05). In the safety assessment of the constructs, the peak stress of plates between constructs was found to not be statistically significantly different under a doubled physiological load (P > 0.05). The average stress of the plates’ elements exceeding the allowable stress was analyzed, and no statistically significant differences were found between the two constructs under axial compression stress conditions (P > 0.05). The average stress of the plates’ elements in the redesigned plating construct under torsional stress conditions was 3.08% less than that of the locked plating construct (P < 0.05). Under the double physiological load condition, 89% of the elements of the plate in the redesigned plating construct and 85% of the elements of the plate in the locked plating construct were lower than the maximum safe stress of the plate, which was 410 MPa (secondary allowable stresses)